Long-term Social, Economic and Fiscal Effects of Immigration into the EU: The Role of the Integration Policy - d'Artis Kancs; Patrizio Lecca (Publications Office of the European Union, 2017)
The issues of the forced migration and integration of refugees in the EU society and labour markets are high on the policy agenda. Apart from humanitarian aspects, a sustainable integration of accepted refugees is important also for social, economic, budgetary and other reasons. Although, the potential consequences of the refugee acceptance are being often discussed, little scientific evidence has been provided for the policy debate so far in the context of the current refugee crisis. The present study attempts to shed light on the long-run social, economic and budgetary effects of the rapidly increasing forced immigration into the EU by performing a scenario analysis of alternative refugee integration scenarios. Our simulation results suggest that, although the refugee integration (e.g. by the providing language and professional training) is costly for the public budget, in the medium- to long-run, the social, economic and fiscal benefits may significantly outweigh the short-run refugee integration costs. Depending on the integration policy scenario and policy financing method, the annual long-run GDP effect would be 0.2% to 1.4% above the baseline growth, and the full repayment of the integration policy investment (positive net present value) would be achieved after 9 to 19 years.
Keywords: F22; J6; J11; J24; 330; Migration; refugees; social inclusion; labour market; integration policy; modelling; scenario analysis; macroeconomic model